Incremental value of three‐dimensional transthoracic echocardiography over the two‐dimensional modality in the assessment of right heart compression and dysfunction produced by pectus excavatum. Issue 1 (28th December 2018) - Salama, Ahmed Y.; Arisha, Mohammed J.; Nanda, Navin C.; Klas, Berthold; Ibeche, Bashar; Wei, Benjamin
Abstract : The usefulness of two‐dimensional transthoracic echocardiography (2DTTE) in the assessment of right heart compression and dysfunction produced by pectus excavatum chest wall deformity has been well described in the literature by several investigators. However, there is a paucity of reports describing incremental value of live/real time three‐dimensional transthoracic echocardiography (3DTTE) over the two‐dimensional technique in the evaluation of right heart function in these patients. We present a severe case of pectus excavatum chest wall deformity in a young male, in whom 3DTTE provided incremental value over standard 2DTTE in assessing compression of the right heart before surgery and marked improvement in right heart function parameters following surgical repair. In addition, an updated summary of salient features of this deformity, including 2D and 3DTTE findings as well as right heart echocardiographic parameters by both 2D and 3DTTE in normal/healthy subjects summarized from the literature have been provided in a tabular form for comparison.